Morbidity of medical staff depending on nutritional characteristics and use of vitamins - E. A. Medvedeva; G. G. Maryin; O. A. Svitich; K. A. Zykov; A. A. Ploskireva; T. A. Chebotareva; O. A. Gruzdeva; D. A. Nazarov; I. O. Volynkov; A. A. Leshchenko (Журнал инфектологии)
Purpose of the study: to analyze the influence of dietary habits and the use of biologically active additives (BAAs) as a factor influencing the risk of COVID-19 in medical workers.Materials and methods: A longitudinal online study was conducted from March to April 2022. Incidence was assessed as the percentage of COVID-19 cases among the total number of respondents. Characteristics of methods for studying actual nutrition were carried out using the method of retrospective recording of nutrition (method of analysis of frequency of consumption).Results: respondents who took vitamin D in a prophylactic dosage were less likely to get sick with COVID-19 (confirmed SARS-CoV-2) – 35.9% did not get sick with SARSCoV-2; and those who didn’t take it – only 5.85%; p <0. 0001. Taking vitamin D reduced the odds (OR) of developing COVID-19 by 9.011 times (95% CI 4.581–17.710); and the relative risk of developing the disease by 46.5%. Prophylactic use of multivitamin complexes did not affect the risk of COVID-19 (p=0.14). It was found that the use of vegetables in the daily diet reduces the chance (OR) of the occurrence of clinical manifestations of a new coronavirus infection by 1.948 times (95% CI 0.845–4.492); and when consuming more than 400 grams per day – by 2.530 times (95% CI 1.015– 6.306). Daily consumption of green salads reduces the risk of disease by 29.5%.Conclusion: impaired nutritional status leads to dysregulation of inflammation and oxidative stress; increasing susceptibility to infection and the risk of worsening the disease. The role of proper nutrition should not be overlooked and the use of vitamin D as a non–specific prophylaxis supports the immune system.